Analysis, control and optimal operations in Hybrid Power Systems : advanced techniques and applications for linear and nonlinear systems - Shayeghi, Hossein; Mahdavi Tabatabaei, Naser (Green Energy and Technology,, 2013)
'Analysis, Control and Optimal Operations in Hybrid Power Systems' explains and analyzes the dynamic performance of linear and nonlinear systems for Power Systems (PS) and Hybrid Power Sources (HPS). System stability is important for both PS operation and planning, and therefore this book places emphasis on understanding the principles that underlie HPS stability. It opens with an exploration of basic concepts using mathematical models and case studies from linear and nonlinear systems, and continues with complex models and algorithms from the PS field. Useful features include: (1) a progressive approach from simplicity to complexity; (2) a deeper look into the advanced aspects of stability theory; (3) a detailed description of system stability using the state space energy conservation principle; (4) a review of research in the field of PS stability analysis; (5) advanced models and algorithms for Transmission Network Expansion Planning (TNEP); (6) stability enhancement including the use of the Power System Stabilizer (PSS) and Flexible Alternative Current Transmission Systems (FACTS); and (7) an examination of the influence of nonlinear control on fuel cell HPS dynamics. This book offers an accessible approach and is an essential resource for both undergraduate and graduate students of electrical engineering. It also provides a comprehensive reference text for practising engineers as well as researchers working in the field of power system technologies.